A cross-sectional descriptive analysis of portrayal of autism spectrum disorders in YouTube videos: A short report. (January 2020) - Bellon-Harn, Monica L; Manchaiah, Vinaya; Morris, Lekeitha R
Professionals have expressed concerns about the quality of autism-related information available from Internet-based sources. The purpose of this study was to examine the source, content, usability, and actionability of autism spectrum disorder–related information contained in 100 different videos directed to families of children with autism spectrum disorder uploaded to YouTube. Upload sources were identified, and video content was coded. Understandability and actionability of the videos were examined using Patient Education Materials Assessment Tool for Audiovisual Materials. The collective number of views of the videos was almost 100 million. The length of videos was 691.17 min (i.e. 11.5 h) with the shortest video being 30 s and the longest video being 37.36 min. The YouTube videos related to autism spectrum disorder covered a range of issues, although much of the content was focused on signs and symptoms. No difference in content reporting was noted based on sources for most categories, although differences were noted in some categories (e.g. professionals mentioned diagnosis and resources more frequently). Poor understandability and actionability scores (i.e. below 70%) were reported for all videos regardless of video source. However, the videos generated by the professionals were superior in terms of understandability. Study implications and recommendations for further research are discussed.